PENDAMPINGAN PENGELOLAAN SISTEM AIR BERSIH DI BANJAR PENGANGGAHAN DESA TENGKUDAK KECAMATAN PENEBEL KABUPATEN TABANAN - I M. Astika; I G. K. Sukadana; M. Suarda; I P. Lokantara; I .G. P. Agus Suryawan (Buletin Udayana Mengabdi, 2013)
Penganggahan village consists of 174 households, with 870 populations. Based on the survey and discussionswith the society members, it can be identified that the problems of dimension of broncaptering is so small thatit catches water from the source is not adequate, however the over flow occurs in reservoir especially duringlow usage at night time. In order to overcome such problems in the village, efforts are conducted by enlargingthe capacity of broncaptering. By increasing the capacity of the broncaptering it will increase the supply of cleanwater for the community. It was done by devising a new reservoir to accommodate the excess water, especiallyat night, with the broncaptering and new reservoirs, Penganggahan village community can be fulfilled especiallyat peak usage in the morning and evening. The evaluation shows that the distribution of water to consumers havebeen very prevalent in the area of the highest and lowest areas.